PERAN ORANG TUA DALAM PENDIDIKAN KARAKTER ANAK DI DESA PERLANAAN DUSUN IV KABUPATEN SIMALUNGUN SUMATERA UTARA - Tama Irhamsyah; Armigel Darsa (Jurnal At-Tabayyun, 2022)
Parents are one of the first and most important educational institutions in a child, because a child is raised and born from parents, and will develop into adulthood. The character values ​​that must exist in children are the value of conscience and the value of giving. Conscience values ​​such as courage, honesty, love of peace. While the value of giving such as, loyal, trustworthy, respectful, polite, friendly and kind. The type of research that the researcher conducts is field qualitative research (field research), which is a study that aims to study intensively about the background of the current situation and the interactions of individuals, groups, institutions and society. With interviews with some parents in Perlanaan Village, parents do not understand the importance of forming children's character and assume that character building is only in formal education (schools) and children are not given enough attention or are not educated optimally so that children have bad characters. While this research model is qualitative. Qualitative is a research model that seeks to uncover phenomena, holistically by describing them through non-numeric language in contexts and natural paradigms.